2007
DOI: 10.1088/0031-9155/53/1/013
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of neutron spectral fluence, radiation weighting factor and ambient dose equivalent for a passively scattered proton therapy unit

Abstract: Stray neutron exposures pose a potential risk for the development of secondary cancer in patients receiving proton therapy. However, the behavior of the ambient dose equivalent is not fully understood, including dependences on neutron spectral fluence, radiation weighting factor and proton treatment beam characteristics. The objective of this work, therefore, was to estimate neutron exposures resulting from the use of a passively scattered proton treatment unit. In particular, we studied the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 32 publications
7
73
1
Order By: Relevance
“…This is in good agreement with previous H/D determinations made in the presence of a phantom. Specifically, measured H/D values from Yan et al (2002) and simulated H/D values from and Zheng et al (2008) ranged from 1 mSv Gy −1 to 15 mSv Gy −1 , depending on the location and other variables.…”
Section: Discussionmentioning
confidence: 99%
“…This is in good agreement with previous H/D determinations made in the presence of a phantom. Specifically, measured H/D values from Yan et al (2002) and simulated H/D values from and Zheng et al (2008) ranged from 1 mSv Gy −1 to 15 mSv Gy −1 , depending on the location and other variables.…”
Section: Discussionmentioning
confidence: 99%
“…This underestimation is greatly reduced at the out‐of‐field location, since the evaporation neutrons with energy spectrum peaked around 1 MeV are significant 16 , 20 . Neutron H measured by etched track detector, which can measure neutrons up to at least 40 MeV was compared extensively with REM500 measurement in previous study (20) .…”
Section: Methodsmentioning
confidence: 99%
“…The value decreased significantly with lower beam energy and increasing distance of fetus from the field edge. There are other studies of out‐of‐field secondary neutron both with Monte Carlo (MC) calculations or experimental measurements that could be used to estimate the neutron H to the fetus for passive scattering and uniform scanning beams 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 . However, most of these studies were made for a specific proton beam configuration, and the reported values of neutron H vary markedly because of different machine designs, experimental setups, and measurement instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Monte Carlo methods also turn out to be powerful in complex situations where measurements are difficult to achieve. They also have many other applications in proton therapy: verification of shielding design efficiency (Newhauser et al, 2002), assessment of secondary doses received by proton therapy patients (Agosteo et al, 1998;Jiang et al, 2005;Zacharatou Jarlskog and Paganetti 2008) and neutron fluence and ambient dose equivalent calculations (Zheng et al, 2008;Perez-Andujar et al, 2009). It should be noted that each Monte Carlo model must first be carefully validated with experimental data in order to verify the accuracy of results.…”
Section: Introductionmentioning
confidence: 99%